Dankbaarheid en leierskap: ? Toeligting vanuit die idees van John F. Demartini en ? reformatoriese perspektief daarop (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2013)
John F. Demartini is a prominent author on the theme of gratitude, albeit not from a reformational Christian perspective. The concept of thankfulness also figures prominently in the reformational Christian tradition. In this overview article the concept of gratitude is analysed using the ideas of Demartini as well as the reformational Christian perspective on it. This exposition is then used to relate gratitude to leadership and to indicate several implications thereof by which leadership theory can be enriched.